Leadership Styles and Their Effects in Northwest Romanian Multinational Companies - Mircea, Cristina A.; Toader, Diana-Cezara; Rădulescu, Corina M. (Business and Economic Research, 2024)
<span style="color: #000000; font-family: Verdana, Arial, Helvetica, sans-serif; font-size: 10px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial; display: inline !important; float: none;">Multinational organizations are considered among the best-performing organizations, both through organizational culture, politics, and education. The management functions of these organizations also generate effective leadership that largely determines the organizational performance and success of the companies. The management performance of managers in these organizations is measured by criteria that influence work efforts, effectiveness, and employee satisfaction. The purpose of this paper is an analysis of leadership styles and their effects on Northwest Romanian multinationals. In this sense, the research aims to fill the gaps in the specialized literature in the field. The research was based on instruments specific to the study of leadership styles,by applying a questionnaire to 140 leaders from 24 multinationals operating in NW Romania. The analysis was made through the prism of the correlations between the attributes and behaviors of the leaders and the results of these behaviors, respectively, the performance indicators. These quantitative data have statistics so as to identify the specific relationships between the leadership styles and their results. Also, the differences in the results were analyzed according to the sectors of activity, industry, and services in which these leaders operate. The results showed extremely small differences, which proves that the effects of leadership styles are significantly equal, regardless of the activity sector of the multinational organizations. The importance of the empirical study resides in the results of the analysis, which can lead to the promotion of effective leadership both in the studied region and in the entire country, as well as in other types of organizations and institutions.